2015
DOI: 10.9775/kvfd.2015.14238
|View full text |Cite
|
Sign up to set email alerts
|

Geleneksel Türk Fermente Et Ürünlerinde (Sucuk ve Pastırma) Salmonella spp., Listeria monocytogenes, Escherichia coli O157 ve Nitrat-Nitrit Varlığı

Abstract: Turkish sucuk and pastırma are traditional meat products commonly consumed in Turkey. These products are generally known as dry fermented meat products (FMP), fermented and ripened naturally. Curing is a preparation method for FMPs used for prolonging shelf life. As well as additives such as nitrate and nitrite are used to obtain the desired colour and flavour, also inhibit the mentioned bacteria. Despite the advantages of the curing agents, FMPs may pose a risk for human health via uncontrolled (out of limits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Similarly, Sancak et al (2008) reported that nitrite and nitrate contents of 40 sucuk samples obtained from the local market in Van ranged from 0.80 to 82.13 mg/kg and 1.56 to 553.18 mg/kg, respectively. Likewise, Buyukunal et al (2016) indicated that nitrite values of 132 sucuk samples collected from producers and retailers in several cities ranged from 6.41 to 90.02 mg/kg and 28.10 to 174.62 mg/kg. In another study, Doğu et al (2002) also stated that nitrite values of 30 sucuk samples collected from 5 high capacity meat plants in Afyon were between 41.80 and 631.03 mg/kg.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Sancak et al (2008) reported that nitrite and nitrate contents of 40 sucuk samples obtained from the local market in Van ranged from 0.80 to 82.13 mg/kg and 1.56 to 553.18 mg/kg, respectively. Likewise, Buyukunal et al (2016) indicated that nitrite values of 132 sucuk samples collected from producers and retailers in several cities ranged from 6.41 to 90.02 mg/kg and 28.10 to 174.62 mg/kg. In another study, Doğu et al (2002) also stated that nitrite values of 30 sucuk samples collected from 5 high capacity meat plants in Afyon were between 41.80 and 631.03 mg/kg.…”
Section: Resultsmentioning
confidence: 99%
“…However, this change in the amount of added nitrite will vary for the different categories of the products and will strongly depend on the recommendations for the microbiological safety as well as other factors such as storage temperature, water activity, and pH value [6]. The possibility of reduction of nitrite addition is analyzed by scientists for fermented meat product [11][12][13] and cooked meat product [14]. As it could be noted, a problem with nitrite addition to meat products still exists and various methods of replacement of this substance are still considered [15].…”
Section: Introductionmentioning
confidence: 99%
“… Category Area Mean nitrite (mg kg −1 ) Mean nitrate (mg kg −1 ) References Raw meat Khartoum, Sudan Minced meat 42 / Adam et al (2016) Iran Beef 38.7 Beef 83.5 Bahadoran et al (2016) Lamb 49.6 Lamb 74.3 Ground mixed meat 37.2 Ground mixed meat 124 Chicken meat 41.8 Chicken meat 133 Fish 33.9 Fish 55.6 Finland Poultry 22.4 / Suomi et al (2016) Reindeer 12.0 / Sydney/Australian Minced beef 0 Minced beef 18.7 Hsu et al (2009) Beef medallion 0 Beef medallion 38.5 Cooked meat Henan/China Boiled beef 63. 91 / Liang et al (2016) Cured meat products Turkey Pastırma 4.26–46.28 Pastırma 64.12–187.66 Büyükünal et al (2016) Chengdu/China cured meat products 4.0–8.7 / Ji et al (2020a) Philippines Dumingag Chorizo 0.76–1.02 / ( Neri and Patalinghug, 2021 ) Molave Chorizo 0.15–1.73 Pagadian Chorizo 4.59–39.07 Molave Longaniza 0.55–2.54 Pagadian Longaniza 3.40–32.8 USA Meat products 0.64–7.31 Meat products 14.81–78.81 Keeton et al (2009) Sauced and stewed meat products Finland Marinated pork 11.0 / Suomi et al (2016) <...…”
Section: Nitrite and Nitrate In Meat And Meat Productsmentioning
confidence: 99%